2019
DOI: 10.1371/journal.pone.0221908
|View full text |Cite
|
Sign up to set email alerts
|

Association of iron deficiency anemia with tuberculosis in Taiwan: A nationwide population-based study

Abstract: Background Iron deficiency is associated with decreased cellular immunity, which may predispose patients with iron deficiency anemia (IDA) to increased risk of developing tuberculosis (TB). This study investigated the relationship between newly diagnosed IDA and TB infection in Taiwan. Methods The study included data on 21,946 patients with incident IDA and 87,555 non-IDA controls from a national database covering the period 2000–2012. IDA and non-IDA subjects were matc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Of the included 17 articles, 2 (11.8%) research articles were published in years of 2005 [ 27 ] and 2011 [ 28 ] (one in each year’s) while 5 (29.4%) of them were published in the year of 2013 [ 29 , 31 , 32 , 33 , 35 ] and 1 (5.9%) of the research articles was published in the year of 2014 [ 11 ]. Nine (52.9%) of the included articles were published between 2015 and 2019 (4 (23.5%) in 2015 [ 20 , 21 , 30 , 34 ], 2 (11.8%) in 2016 [ 22 , 24 ], and 3 (17.6%) in 2019 [ 10 , 17 , 23 ]). Three of the included studies were cross-sectional studies and were conducted in South Africa [ 11 ], Cameroon [ 29 ], and Nigeria [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the included 17 articles, 2 (11.8%) research articles were published in years of 2005 [ 27 ] and 2011 [ 28 ] (one in each year’s) while 5 (29.4%) of them were published in the year of 2013 [ 29 , 31 , 32 , 33 , 35 ] and 1 (5.9%) of the research articles was published in the year of 2014 [ 11 ]. Nine (52.9%) of the included articles were published between 2015 and 2019 (4 (23.5%) in 2015 [ 20 , 21 , 30 , 34 ], 2 (11.8%) in 2016 [ 22 , 24 ], and 3 (17.6%) in 2019 [ 10 , 17 , 23 ]). Three of the included studies were cross-sectional studies and were conducted in South Africa [ 11 ], Cameroon [ 29 ], and Nigeria [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is also a known risk factor for some chronic diseases [ 41 ]. In the current systematic review and meta-analysis, majority of the included studies showed that anemia was a higher predicator of TB [ 10 , 11 , 17 , 22 , 27 29 , 30 , 31 ]. However, some studies showed that anemia was not the risk of TB [ 20 , 24 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, this process promotes HIV replication through modulation of host redox metabolism, promoting lymphocyte and macrophage-mediated inflammatory response [ 63 ]. In comparison to individuals with mono-infections, those with HIV-TB co-infection express higher levels of inflammatory cytokines such as IL-6, TNF-ɑ, IL-10, and IL-1-β ( Figure 3 ) [ 64 , 65 , 66 , 67 ]. As a consequence of chronic SI, anemia may develop and impact treatment success with antitubercular and antiretroviral therapy, in addition to the risk of IRIS development (reviewed in [ 68 ]).…”
Section: Opportunistic Infection In Hiv and Its Impact On The Inflmentioning
confidence: 99%